Design and implementation of a closed-loop static balance system for YICAL Leg II - Broas, Raymond Alvin L.
Bipedal robots offer greater flexibility and a wider range of movements over certain terrains compared to non-legged or wheeled robots. Add to this the human interest to mimic themselves in robots, many universities and research centers around the world have dedicated time and resources in studying bipedal robots. The most current one, the YICAL Leg 2, is built along with the many improvements and modifications from its predecessor, the YICAL Leg 1. An attitude estimation of the system utilizing an accelerometer and gyroscope was developed for the platform. However the output of this system has yet to be implemented in control of the biped. This project aims to introduce static balance to the YICAL Leg II by utilizing the attitude measurement unit and joint angle sensors. The data from these sensors will be collected via analog-to-digital conversion and Serial Peripheral Interface (SPI). The collected data will then be passed to theTMS320F2812 digital-signal processor to determine the state of the biped. Balancing and state estimation algorithms will then be utilized to enable the biped to sense and react accordingly to certain external forces thereby giving the robot the ability to regain balance.